Nickel ion release from stainless steel brackets in chlorhexidine and Piper betle Linn mouthwash - Tanti Deriaty; Indra Nasution; Muslin Yusuf (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Orthodontist prescribe mouthwash for their patients especially since most of patients do not have a satisfactory oral hygiene and have high risk of dental caries. Stainless steel brackets that exposed by mouthwash may have nickel ion release. Corrosion and nickel ion release can induced allergic reaction and make more friction during orthodontic treatment. Purpose: This study aimed to measure nickel ion release of stainless steel bracket that immersed in chlorhexidine and Piper betle Linn mouthwash. Methods: Thirty-six stainless steel bracket immersed in artificial saliva, chlorhexidine, and Piper betle Linn mouthwash. All brackets stored in incubator for 1, 3, 5, and 7 weeks. Nickel ion release was measured by Atomic Absorption Spectrophotometry (AAS). Results: The results showed a significant differences of nickel ion release in all groups (p<0.05). Conclusion: In conclusion, among the mouthwash, chlorohexidine has the highest nickel ion release from stainless steel brackets, followed with Piper betle Linn mouthwash.